Mastering KVM virtualization : design expert data center virtualization solutions with the power of Linux KVM /: design expert data center virtualization solutions with the power of Linux KVM. (2020) - Dakic, Vedran; Chirammal, Humble Devassy; Mukhedkar, Prasad; Vettathu, Anil
No abstract available